2020
DOI: 10.3390/molecules25030590
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of the Nitroso-Sulfide Signaling Pathway in the Vasomotoric Effect of Garlic Juice

Abstract: The beneficial cardiovascular effects of garlic have been reported in numerous studies. The major bioactive properties of garlic are related to organic sulfides. This study aimed to investigate whether garlic juice works exclusively due to its sulfur compounds or rather via the formation of new products of the nitroso-sulfide signaling pathway. Changes in isometric tension were measured on the precontracted aortic rings of adult normotensive Wistar rats. We evaluated NO-donor (S-nitrosoglutathione, GSNO)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Our previous studies showed an obvious interaction between two important vasoregulatory molecules, NO and H 2 S, and their pathways and suggested the existence of a coupled nitroso–sulfide signaling pathway [ 24 , 25 ]. Herein, we confirmed that the heterogeneity of specific nitroso–sulfide vasoactive signaling exists depending on the occurrence of different pathological stages, e.g., hypertension or increased plasma glucose levels [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed an obvious interaction between two important vasoregulatory molecules, NO and H 2 S, and their pathways and suggested the existence of a coupled nitroso–sulfide signaling pathway [ 24 , 25 ]. Herein, we confirmed that the heterogeneity of specific nitroso–sulfide vasoactive signaling exists depending on the occurrence of different pathological stages, e.g., hypertension or increased plasma glucose levels [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, relaxation induced by the S/GSNO products was not significantly affected by the presence of cPTIO, indicating that a portion of the relaxation induced by reaction products was mediated by an alternative mechanism, which might directly activate soluble guanylate cyclase without releasing free NO. Moreover, in our recent study we recorded that the hyperpolarization of smooth muscle cells after K + -channel activation played no significant role in S/GSNO product-induced relaxation in normotensive rats [ 34 ]. In the conditions of arterial hypertension, using renal arteries isolated from spontaneously hypertensive rats (SHR) we found out that the pre-treatment with ODQ, inhibitor of soluble guanylate cyclase, significantly inhibited the vasorelaxant effect induced by the S/GSNO products so indicating the involvement of the cGMP activation in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Green leaves from garlic foliage (Yoshimoto et al, 2015) Reduce the blood pressure and prevent oxidative stress GPH-P (pepsin) y GPH-T (trypsin) Garlic residuals (Gao et al, 2020) Vasomotoric Organic sulfides nitroso-sulfide Garlic juice (Berenyiova et al, 2020) Inflammation, Obesity and Cardiovascular Disease Organosulfur compounds, alk(en)yl-Lcysteine sulfoxides (ACSOs), alliin, alliinase Garlic bulbs (Quesada et al, 2020) Inhibited excessive adipogenesis obesity…”
Section: Sulfurmentioning
confidence: 99%